Dynamics of international labour migration of Sri Lanka - De Silva, I.; Siriwardhane, D. (My University, 2012)
The objective of this study is to examine the recent patterns of international labour migration dynamics of Sri Lanka to understand the issues related to the recent migration. The study primarily relies on secondary data collected from a number of public authorities. The descriptive approach is employed in analyzing data to achieve the objective. Results of the study show that international migration has been rapidly increasing during past years. Migration stock and flow of Sri Lanka have been highly represented by female migrants. However, with the government intervention in the past few years, the proportionate of female migrants in the migration flow has decreased. Middle East as the common destination absorbs a significantly large share of the labour migrants. However, a proper labour market analysis is essential to identify emerging labour markets to gain the maximum benefit of labour migration. While remittances make a strong economic impact, a significant social impact of the labour migration in the country can be observed.
Keywords: Labour Migration, structural change, labour force, female participation